Cyclic behavior of glulam connections with inclined self-tapping screws - Jia Lei; Jingkang Lin; Shuke Jia; Zhiyuan Chen; Feibin Wang; Zeli Que (Journal of Asian Architecture and Building Engineering)
Glued laminated timber (glulam) structures are attracting increased attention in seismic applications due to their sustainability and high strength-to-weight ratio. This study investigates the cyclic and static shear performance of glulam joints connected with inclined self-tapping screws (STS), aiming to identify optimal connection configurations for improved seismic resilience. Four types of inclined STS configurations were experimentally assessed under low-cycle repeated loading, simulating seismic stress conditions. Key mechanical properties such as energy dissipation, stiffness, ductility, and load-bearing capacity were analyzed in detail. Results show that under cyclic loading, all joint configurations exhibited stable hysteretic behavior. The ordinary screw joint with shear loading (OSJ-S) demonstrated the highest energy dissipation during the initial loading cycles, while the inclined screw joint under compression-shear loading (ISJ-C) exhibited superior energy retention at the yield stage. The inclined screw joint under tension-shear loading (ISJ-T) and the inclined screw joint under X-shear loading (ISJ-X) effectively mitigated stiffness degradation over multiple cycles, improving joint stability. Additionally, inclined screws – particularly at a 45° angle – significantly enhanced initial joint stiffness, with the highest stiffness observed in tension-shear connections. This study provides critical insights into the mechanical behavior of inclined STS in glulam joints, establishing a foundation for optimizing timber connection design in seismic applications.